It happened one night [videorecording (DVD)] - Capra, Frank, 1897-1991; Gable, Clark, 1901-1960; Colbert, Claudette; Connolly, Walter, 1887-1940; Adams, Samuel Hopkins, 1871-1958 (Columbia classics, 1999)
A rich young woman marries an idle playboy against her father's will. Her father holds her captive on his yacht but she escapes and, while on her way to New York, becomes entangled with an unemployed news reporter.